Konventionelle figurative enheder (idiomer) i Jysk Ordbog og andre større ordbøger - Arboe, Torben (Nordiske Studier i Leksikografi, 2018)
Inside the framework of cognitive linguistics and lexical semantics the study employs a theory of conventional figurative units, e.g. metaphors and similes, based on a conceptual theory of metaphors. The lexical mate-rial is found in the card index and files of the Jysk Ordbog (Dictionary of the Jutland Dialects); it consists of idioms from a broad range of seman-tic fields, arranged in oppositions as 'richness vs. poorness', 'cleverness vs. foolishnes', and it covers especially topic groups of the daily work and life on farms, in villages etc. of the countryside. The study shows how the idioms are treated in the entries of Jysk Ordbog, and special attention is given to instances of polysemy due to figurative use of word; this may require addition of a submeaning to a lexical entry. The results are sum-marized in an overview chart for the key lexemes of the idioms in the re-spective semantic fields.